Redistribution, In-Kind Transfers and Matching Grants when the Federal Government Lacks Information on Local Costs - Sören Blomquist; Luca Micheletto (Uppsala University, Department of Economics, 2004)
Recent literature on optimal nonlinear taxation has shown that in models with a single level of government public provision of private goods can help redistribution by mitigating self-selection constraints. The aim of the present paper is to extend the analysis to a fiscal federalism setting with two levels of government. To accomplish this goal we start by explicitly modelling the informational asymmetry that in our framework motivates decentralization in the first place: the lower level is able to observe the local costs of production, which vary across localities, but the central level does not. Then, using an extended version of the optimal income taxation model with two ability types, we show that even though it is the lower level that is responsible for the public provision of private goods, in-kind transfers can still help the federal level to redistribute between high- and low skilled individuals. Finally, we characterize the optimal marginal tax rates, which take a different form from that of a unitary model, and the optimal matching grants. The latter, in particular, have a very different structure than the one derived in previous fiscal federalism studies. We also find that it is vital to model informational asymmetries between the central and the local level explicitly. Models where the informational asymmetry is not explicit might have very little to say about decentralization in economies where the local level has an informational advantage over the central level.
Keywords: H21; H42; H77; 330; Optimal taxation; in-kind transfers; public provision of day care; fiscal federalism; Optimale Besteuerung; Finanzbeziehungen; Finanzausgleich; Öffentliche Güter; Sachtransfer